Tracing Signs of Urbanity in the Finnish Fiction Film of the 1950s: Toward a Multimodal Analysis of Audiovisual Data - Grósz Tamás; Kallioniemi Noora; Kiiskinen Harri; Laine Kimmo; Moisio Anssi; Römpötti Tommi; Virkkunen Anja; Salmi Hannu; Kurimo Mikko; Laaksonen Jorma (Sweden, 2022)
This paper traces signs of urban culture in Finnish fiction films from the 1950s by drawing on a multimodal analysis of audiovisual content. The Finnish National Filmography includes 208 feature films released between 1950–1959. Our approach to the automatic analysis of media content includes aural and visual object recognition and speech recognition. We concentrate on features that epitomize urbanity, including visual objects, such as forms of transportation (cars, horses) and sounds (rural and urban sounds, speech). Based on the scores and frequencies of these recognitions, we observe quantitative changes that took place during the 1950s. The paper demonstrates that aural and visual object recognition, as well as speech recognition, can successfully be applied in film historical analysis. The overall results support the idea that Finnish filmmakers fueled the imagination of urban life in the 1950s, paving the way for modern technologies and gradually pushing aside the signs of rural life.
The 6th Digital Humanities in the Nordic and Baltic Countries Conference (DHNB 2022), Uppsala, Sweden, March 15-18, 2022